Dating Apps dalam Perspektif Hadis: Kajian Tematik Zina di Era Digital - Rozaq, Muhammad Abdur; Muzakki, Muhammad Asgar; ‘Ash, Abil (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
Technological advancements have influenced human interactions, including partner searches through dating apps. Although dating apps offer certain benefits, they also raise concerns regarding behaviors that verge on zina (adultery), especially within Muslim societies. This study aims to examine the Islamic perspective, particularly through thematic hadith, on the use of dating apps in relation to zina behavior prohibited by the Qur'an and As-Sunnah. The research employs a library research method, gathering data from books, journals, and other relevant literature sources. A thematic-conceptual approach in hadith studies is utilized to analyze various forms of zina and how the use of dating apps can potentially lead to such behaviors. The findings of this study indicate that using dating apps, whether for finding a life partner or for entertainment, can create opportunities for various forms of zina, including zina of the eyes, zina of the tongue, and zina of the heart. However, the use of dating apps can be acceptable in Islam if conducted with good intentions, in accordance with sharia, maintaining ethics, and avoiding actions that approach zina. Therefore, the importance of education and self-awareness in using technology is emphasized, along with the role of the community and scholars in providing guidance aligned with Islamic teachings.Abstrak: Kemajuan teknologi telah mempengaruhi cara manusia berinteraksi, termasuk dalam konteks pencarian pasangan melalui dating apps. Meskipun memiliki manfaat, dating apps juga menimbulkan kekhawatiran terkait risiko perilaku yang mendekati zina, terutama dalam masyarakat Muslim. Studi ini bertujuan untuk mengkaji perspektif Islam, khususnya melalui hadis tematik, terhadap penggunaan dating apps dalam kaitannya dengan perilaku zina yang dilarang oleh Al-Qur'an dan As-Sunnah. Penelitian ini menggunakan kajian pustaka (library research) dengan mengumpulkan data dari buku, jurnal, dan sumber literatur lainnya yang relevan. Pendekatan yang digunakan adalah tematik-konseptual dalam kajian hadis, untuk menganalisis berbagai bentuk zina dan bagaimana penggunaan dating apps dapat berpotensi menimbulkan perilaku tersebut. Hasil kajian ini menunjukkan bahwa penggunaan dating apps untuk mencari pasangan hidup maupun sekadar hiburan dapat membuka peluang terjadinya berbagai bentuk zina, termasuk zina mata, zina lisan, dan zina hati. Namun, penggunaan dating apps dapat diterima dalam Islam jika dilakukan dengan niat yang baik, sesuai dengan syariat, menjaga etika, dan menghindari hal-hal yang mendekati zina. Oleh karena itu, pentingnya edukasi dan kesadaran diri dalam penggunaan teknologi juga ditekankan, serta peran komunitas dan ulama dalam memberikan panduan yang sesuai dengan ajaran Islam.